Społeczeństwo informacyjne a kultura konsumpcyjna - Sułkowski, Łukasz (Information society versus consumer culture, 2006)
In relations between the development of information society and the expansion of consumer culture we lace a paradox. Network organizations and information society transform larger and larger amounts of information and create new channels of communication, which docs not lead, however, to the growth of the rationality of activities. It appears that information socjety strengthens the development of consumption culture - the culture which leads to ostentatious, wasteful and irrational resource consumption.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 221-227